Advances in single crystals and thin films of chiral hybrid metal halides. (March 2022) - Guo, Zhihang; Li, Junzi; Chen, Rui; He, Tingchao
Abstract: Chiral organic–inorganic hybrid metal halides (HMHs), as an emerging class of chiral semiconductor materials, have attracted unparalleled interest from multi-purpose perspectives, as a result of their easily accessible solution-grown methods, plentiful chemical structure and composition, as well as unique and exciting optoelectronic properties. Recently, substantial progress has been made in the synthesis of chiral HMHs, spectroscopic characterization and fabrication of optoelectronic devices. Although several reviews about the chiroptical properties and applications of chiral HMHs have been published, the comprehensive summary of the basic structural frameworks, fundamental physics and strategies for the modulation of optical activity, which are vital for the design of chiral HMHs and development of relevant optoelectronic applications, are still insufficient. In this review, we summarize the research progress from fundamentals to applications for the single crystals and thin films of chiral HMHs that are conducive to the development of practical optoelectronic devices. First, diverse structural frameworks and synthetic methods of chiral HMHs are systematically summarized. Afterward, fundamental physics and strategies for the modulation of optical activity as well as their related optoelectronic applications are comprehensively reviewed. Finally, we put forward the current challenges in this rapidly evolving field and present an outlook on future prospects to further develop chiral HMHs for various applications. Graphical abstract: Chiral hybrid metal halides (HMHs) have attracted unparalleled interest due to their unique optoelectronic properties and intriguing application prospects. This review presents a comprehensive summary on the advances in the single crystals and thin films of chiral HMHs, with a focus on their structural frameworks, synthetic methods, fundamental physics and strategies for the modulation of optical activity as well as the related optoelectronic applications. Image 1